Adaptive Kinetic Architecture and Collective Behavior: A Dynamic Analysis for Emergency Evacuation - Angella Johnson; Size Zheng; Aiichiro Nakano; Goetz Schierle; Joon-Ho Choi (Buildings, 2019)
Adaptive kinetic architecture has emerged from a need for innovative designs that adapt to the environment and changing needs of the occupants. Architectural design and modes of egress are critical in an emergency. Flocking describes a certain collective behavior where agents are brought together in groups and move as a cohesive unit from place to place. Collective behavior may be observed in microscopic as well as macroscopic environments. Crowd modeling incorporates the study of human behavior, mathematical modeling, and molecular or fluid dynamics. The simulation of agents and their movement in the built environment is beneficial for design professionals, scientists, and engineers. Human behavior in panic situations is notably similar to fluids and molecules. The objective of this research was to evaluate the movement of agents in buildings using discrete dynamic simulation. We used a novel discrete molecular dynamics technique to simulate the evacuation of agents in panic situations. Various adaptive geometric configurations were analyzed for improved crowd flow. Kinetic walls were modeled in order to evaluate design optimization as it relates to rates of egression. This research proposes the use of kinetic walls to improve safety and efficiency during an emergency evacuation. Adaptive geometric configurations show improvements over the conventional design framework.